The effect of international venturing on firm performance: The moderating influence of absorptive capacity - Zahra, Shaker A.; Hayton, James C. (Journal of Business Venturing, 2008)
Companies have vigorously pursued opportunities for profitability and growth through international venturing. Yet, research evidence on the performance benefits of international venturing activities has been contradictory. Applying an organizational learning framework, we propose that the expected effects of international venturing activities on financial performance depend on companies' absorptive capacity. Data from 217 global manufacturing companies show that absorptive capacity moderates the relationship between international venturing and firms' profitability and revenue growth. These results urge executives to build internal R&D and innovative capabilities in order to successfully exploit the new knowledge acquired from foreign markets.